Técnicas de marketing sensorial aplicadas ao desenvolvimento de um rótulo para barra de gergelim e produtos apícolas - Frota, Julynara Alves (2018)
With day-to-day activities filled with increased concern about quality of life, the consumer has been looking for more practical foods such as healthy, nutritional bars that promote improved health. Faced with this increasingly promising market, the food industry makes use of several strategies to attract the consumer, among them the sensorial marketing. The present study aimed to apply sensory marketing techniques in the development of a front label for a food bar containing sesame, bee pollen and honey, verifying its influence on the acceptance of the product. In the development of the frontal label, the techniques of marketing, focus group and online questionnaire were adopted to identify the elements and information to be inserted, and in the evaluation of the acceptance of the bar were used tests of expectation and intention to buy. In the evaluation of the label was used the Likert scale. Through the results obtained with the online questionnaire, the attributes of the product should highlight quality, food safety and taste. The packs must present nutritional information (high in fiber, source of protein, 100% natural, source of minerals, without trans fats and low sodium content), practicality and able to indicate the quality. The consumer suggested, during the focus groups, packages with frosted colors varying in yellowish tones (related to bee products and sesame) and wood (resembling natural products), with at most three complementary nutritional information, and may or may not have the presence of illustrative picture. As far as the sensorial evaluations, analyzed through the hedonic scale for the attributes global impression, appearance, aroma, flavor, sweetness and texture, the observed results were positive with average around 6 (I liked it slightly). For the tests of expectation and intention to buy, before and after the consumption of the product, the label 1 (without information) differed from the others in the acceptance (p≤5). And labels 2 and 3 (with complementary nutritional information - naturally sweetened and antioxidants, respectively) did not differ from each other (p≤5). Therefore, the use of marketing techniques for the elaboration and evaluation of a frontal label helped to identify the elements that must be present on the front label of the food bar and the positive results were reflected through the sensorial evaluation, and later, in the evaluation of the characters present on the label with an average of around 7 (partially agree).